GENDER REPRESENTATION ANALYSIS IN IGCSE ENGLISH AS A SECOND LANGUAGE 5TH EDITION TEXTBOOK - Patty, Anthony Rudolf (ENGLISH JOURNAL, 2023)
The ultimate purpose of the study is to examine gender representative aspects of International General Certificate of Secondary Education English as a Second Language 5th Edition textbook published by Cambridge. This study is aimed at analyzing how gender is portrayed through attributes, actions, and activities, employing Brugeilles and Cromer’s theory of gender description. Utilizing Kripendorff’s content analysis and Bowen’s document analysis, the writer carefully identified the images and the texts which contained attributes, actions, and activities. Then, the writer analyzed each text and image in accordance with Brugeilles and Cromer’s theory. The result revelaed that the textbook portrayed both males and females in the form of images and texts. Besides, both males and females are depicted to suit the activities and the actions, as well as attributes, related to Brugeilles and Cromer’s theory. Females are known to wear make-up and powder. They are also known to be meticulous and patient. Also, they now begin to be involved in activities of which were once identical to males. On the other hand, males are identical to field job. They do activities out of the home more frequently. They also take parts in activities that require power and more energy as males are known to have stronger physical aspects than females. This study also offers its limitations and suggested future research of the topic. Future research may administer investigations with applying Brugeilles and Cromer’s theory of gender description in its entirety.